2004
DOI: 10.2105/ajph.94.10.1736
|View full text |Cite
|
Sign up to set email alerts
|

Pounds Off With Empowerment (POWER): A Clinical Trial of Weight Management Strategies for Black and White Adults With Diabetes Who Live in Medically Underserved Rural Communities

Abstract: Improvement in both weight and glycemia was attainable by lifestyle interventions designed for persons who had type 2 diabetes and lived in rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
270
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(280 citation statements)
references
References 30 publications
6
270
2
Order By: Relevance
“…The feasibility and acceptability of the study were demonstrated by the high retention rates at 3 and 6 months and the positive patient engagement and experience reported during patient interviews. In fact, our retention rates of 96% at 3 months and 92% at 6 months were higher than those reported in most of the previous behavioral lifestyle interventions mediated by technology in obesity and T2DM [23,24], including those in medically underserved communities [25].…”
Section: Discussioncontrasting
confidence: 72%
“…The feasibility and acceptability of the study were demonstrated by the high retention rates at 3 and 6 months and the positive patient engagement and experience reported during patient interviews. In fact, our retention rates of 96% at 3 months and 92% at 6 months were higher than those reported in most of the previous behavioral lifestyle interventions mediated by technology in obesity and T2DM [23,24], including those in medically underserved communities [25].…”
Section: Discussioncontrasting
confidence: 72%
“…receiving appropriate laboratory tests and examinations), and are put on clinically appropriate medication regimens during the medical visit, may not succeed in diabetes self-management in their daily life context. 36,37 Therefore, in addition to ongoing efforts to improve access and quality of care, better tailoring of diabetes self-management regimens through increased integration of the health care system with the community [38][39][40] , improved doctor-patient communication about barriers to adherence 41,42 , and greater involvement of self-management support resources such as nurse educators and health coaches 9,43 may promote improved adherence and outcomes in the face of challenging contextual influences.…”
Section: Discussionmentioning
confidence: 99%
“…Organization, delivery, and funding of lifestyle interventions are all issues that must be addressed. Thirdparty payers may not provide adequate benefits for sufficient MNT frequency and time to achieve weight loss goals (18).…”
Section: Recommendationsmentioning
confidence: 99%